1980
DOI: 10.1103/physrevlett.45.1179
|View full text |Cite
|
Sign up to set email alerts
|

Hot Electron Generation by the Two-Plasmon Decay Instability in the Laser-Plasma Interaction at 10.6 μm

Abstract: Hot electron generation in a long-density-scale-length (~300 pirn) underdense plasma has been studied. For a plasma of maximum electron density of \n c the hot electron emission is localized in the plane of polarization of the incident C0 2 laser and peaked about 45° with respect to the k vector of the laser beam, in both forward and backward directions. These observations suggest that the hot electrons are generated by the twoplasmon decay instability at quarter-critical density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(42 citation statements)
references
References 6 publications
0
42
0
Order By: Relevance
“…2ω p and SRS are of particular interest because subsequent conversion of energy from the electron plasma waves to energetic streaming electrons 18,19,20 could result in significant heating of the compressed fuel, which can reduce gain and prevent ignition. Stimulated Brillouin scattering is expected to only occur at low levels with KrF due to the short laser wavelength and the inclusion of beam smoothing by ISI.…”
Section: Laser-plasma Instabilities For Ftf Developmentmentioning
confidence: 99%
“…2ω p and SRS are of particular interest because subsequent conversion of energy from the electron plasma waves to energetic streaming electrons 18,19,20 could result in significant heating of the compressed fuel, which can reduce gain and prevent ignition. Stimulated Brillouin scattering is expected to only occur at low levels with KrF due to the short laser wavelength and the inclusion of beam smoothing by ISI.…”
Section: Laser-plasma Instabilities For Ftf Developmentmentioning
confidence: 99%
“…Early experiments using CO 2 lasers measured the first hot electrons generated by TPD [16] and the associated electron plasma waves using Thomson scattering [17]. More recent experiments focusing on TPD in direct-drive ignition conditions [18] demonstrated that the efficiency of hot-electron generation scaled with overlapped laser beam intensity [19].…”
mentioning
confidence: 99%
“…In particular, stimulated Raman scattering ͑SRS͒, where the incident photon decays into a scattered photon and a plasmon, and the two-plasmon decay instability ͑TPD͒ which is the parametric decay of an incident laser photon into two plasmons, are relevant processes. [6][7][8][9][10] In long pulse laser-plasma interaction, the dominant production process for 3/2-harmonic radiation was found to be TPD, which occurs resonantly at 1/4n c . 10 With nanosecond and sub-nanosecond pulses, the instability reaches a nonlinear saturation caused by the decay of an electron plasma wave into an ion-acoustic wave and a scattered electron plasma wave ͑Langmuir wave decay instability-LDI͒.…”
mentioning
confidence: 99%